An integrated theory based-educational intervention to change intention to have a child: study protocol of a cluster randomized controlled trial - Maryam Moridi; Maryam Damghanian; Sedigheh Keshaverz (BMC, 2024)
Abstract Background In high- and low-income countries, declining birth rates have become a global concern. Couples do not have enough information about the complications of delaying and reducing childbearing and this leads them to make inappropriate decisions. Therefore, this study aims to evaluate whether an educational program based on integrating the Theory of Planned Behavior (TPB) and the Trans-Theoretical Model (TTM) affects child-free couples' intention to have children and minimizes the consequences of this decline. Methods Thirty couples (intervention, n = 15; control, n = 15) will be enrolled in this cluster randomized controlled trial. After collecting baseline data and separating participants in the pre-contemplation and contemplation stages based on the TTM, the samples were randomly assigned to the intervention and control groups. The intervention group will receive 60-min training based on TPB components for 4 weeks. The first follow-up assessment was performed immediately after the intervention and the final assessment 6 months later. For all 3 time assessments, three questionnaires will be used: The knowledge questionnaire, the TTM, and the TPB questionnaire. The most important consequences are changes in knowledge, attitudes, subjective norms, perceived behavioral control, and stages of intentions to have children. Discussion Decision-makers will use the results of this study as a basis to design appropriate, transparent, and useful policies and interventions to improve or stop the decline of the fertility rate at the national level. Also, this study will help young couples who wish to have a child in their lifetime by providing relevant information so that they do not miss this opportunity and face the consequences of delaying having a child. Trial registration This study was approved by the Iranian Registry of Clinical Trials (IRCT), Number: IRCT20220618055210N2, Date of registration: 2023-10-03